Clinical study of free folded fibular flap reconstruction combined with implant placement for restoration of mandibular defects and occlusal relationships - Zhenghao Ma; Zhiqiang Pan; Yunqi Chen; Luwen Song; Lina Jiang; Jiancheng Li (Frontiers in Oncology, 2026)
Objective To investigate the clinical efficacy of using a digitally designed vascularized folded fibula combined with implant placement, and applying stereophotogrammetry for impression taking to reconstruct mandibular defects and restore patients’ occlusal relationships. Methods The clinical data of 24 patients treated between January 2020 and February 2024 were analyzed, including 16 cases of benign mandibular tumors, 4 cases of medication-related osteonecrosis of the jaw (MRONJ), and 4 cases of osteoradionecrosis (ORN). Three-dimensional reconstruction of the mandible and fibula was performed with digital technology assistance to simulate mandibular tumor resection, fibular harvesting, and implant placement. Various surgical guides were designed and used to complete mandibular reconstruction and implant placement. Phase II implant surgery was performed 4–6 months postoperatively, and stereophotogrammetry was used to obtain impressions for digital design and fabrication of implant crowns to complete the implant-supported prosthetic restoration. Follow-up visits were conducted at 6 months, 1 year, and 2 years after delivery of the implant-supported prosthesis. Results Regarding mandibular defect types, there were 13 cases of Brown Class I defects, 5 cases of Brown Class II defects, and 6 cases of Brown Class III defects. A total of 78 implants were placed in the 24 patients. Six months after delivery of the implant-supported prostheses, all implants and prostheses remained intact. At the 1-year follow-up, one patient presented with a loose implant crown due to loosening of the fixation screw. At the 2-year follow-up, one patient showed significant implant mobility, and the implant was removed. Conclusion For patients with segmental mandibular defects caused by benign lesions and jaw osteonecrosis, the use of a digitally designed vascularized folded fibula combined with implant placement to reconstruct mandibular defects, together with stereophotogrammetry for impression taking, can effectively reconstruct mandibular morphology and occlusal relationships. For functional reconstruction of non-neoplastic mandibular defects or after benign tumor resection, this technique is a precise and reliable treatment option. Trial registration The study was registered in the Chinese Clinical Trial Registry database on August 21, 2020, under the registration number ChiCTR2000035932.